Access to nonisocyanate poly(thio)urethanes: A comparative study. Issue 15 (16th May 2013) - Besse, Vincent; Foyer, Gabriel; Auvergne, Rémi; Caillol, Sylvain; Boutevin, Bernard
ABSTRACT This article describes the synthesis of new cyclic compounds able to react with amines to get nonisocyanate polyurethanes (NIPUs). The contribution of the most studied five‐membered cyclic carbonate was compared to five‐membered cyclic dithiocarbonate analogous and to a six‐membered cyclic carbonate. Difunctional reactive species were obtained by a simple substitution reaction or an efficient thiol–ene coupling reaction. The products, obtained with high yields, were characterized by 1H NMR, 13C NMR, and Fourier tansform infrared spectroscopy analysis. The dicyclocarbonates were then used to synthesize NIPUs by step growth polymerization with several diamines. These materials exhibited glass transition temperatures from 19 to −29 °C, molar mass from 1800 to 20, 400 g mol−1, and a 20% mass loss temperature (Td = 20%) between 249 and 296 °C. Such materials are interesting candidates for coating applications. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3284–3296